Conspecific density drives sex-specific spatial wintertime distribution and hoarding behaviour of an avian predator - Koivisto Elina; Masoero Giulia; Morosinotto Chiara; Le Tortorec Eric; Korpimäki Erkki (BirdLife Finland, 2025)
Most studies on intraspecific competition, i.e., competition among individuals of the same species, have been conducted during the breeding season. Yet, at northern latitudes, intraspecific competition is expected to be particularly strong under the harsh weather conditions of the non -breeding season with limited number of resources available per individual. We studied the food -hoarding behaviour of wintering Eurasian Pygmy Owls (Glaucidium passerinum) along with sex- and age -specific spatial distribution in relation to fluctuating main prey abundance (voles) and conspecific density using a 15 -year dataset. In low vole abundance years, increasing conspecific density reduced the total prey number stored by an owl, suggesting high costs of exploitative competition. The distance between the stores of nearest neighbours was greater when both were females, suggesting that the spatial avoidance is driven by sex -specific competition. However, food stores of females had a larger amount of prey items, especially when the nearest neighbour was of the same sex. The number of stores hoarded by an owl increased with increasing conspecific densities. Distributing the prey items to multiple storesites instead of one (shifting from larder -hoarding towards scatter -hoarding) can help to reduce the overall loss to potential pilfering when conspecific density is high. These results combined suggest that high conspecific density inflames sex -specific interference competition, rather than solely exploitative competition, and in turn drives the observed sex -specific spatial distribution. Adopting a sex -specific spatial distribution according to hoarding and aggressive behaviour can be a way to reduce the severity of intraspecific competition locally and could have cascading effects on the prey community.